2016
DOI: 10.1002/ldr.2668
|View full text |Cite
|
Sign up to set email alerts
|

Continental‐scale Impacts of Livestock Grazing on Ecosystem Supporting and Regulating Services

Abstract: Grazing by livestock supports millions of people worldwide, particularly in drylands, but has marked negative effects on ecosystem services and functions. In Australia, its effects on ecosystem services have not been fully quantified. We examined the extent to which grazing by livestock influenced supporting (productivity, habitat for organisms and biodiversity) and regulating (carbon cycling and hydrological function) services, using data from published and unpublished studies on livestock grazing from a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 65 publications
3
60
0
2
Order By: Relevance
“…LI and MS present higher chl a contents by surface unit than cyanobacteria-dominated biocrusts (Lan et al, 2012). These regulating services, which provide good habitat conditions for plant seeds to germinate (Ferrenberg et al, 2018), can be reduced at moderate-to-high grazing intensities, as recently reported elsewhere (Eldridge & Delgado-Baquerizo, 2017). The grazing effect on BC and BR increased across the grazing gradient at medium and high aridity sites.…”
Section: Grazing Interacts With Aridity To Determine Biocrust Biomasupporting
confidence: 70%
“…LI and MS present higher chl a contents by surface unit than cyanobacteria-dominated biocrusts (Lan et al, 2012). These regulating services, which provide good habitat conditions for plant seeds to germinate (Ferrenberg et al, 2018), can be reduced at moderate-to-high grazing intensities, as recently reported elsewhere (Eldridge & Delgado-Baquerizo, 2017). The grazing effect on BC and BR increased across the grazing gradient at medium and high aridity sites.…”
Section: Grazing Interacts With Aridity To Determine Biocrust Biomasupporting
confidence: 70%
“…Unlike previous case studies assessing grazing effects (e.g. Aguiar et al, 1996;Cipriotti & Aguiar, 2012), or metaanalyses (Eldridge & Delgado-Baquerizo, 2016), our study includes a large number of field sites scattered over a large area comprising a wide variation in environmental conditions and surveyed using a standardized protocol. Thus, it provides important and novel insights into the effects of grazing on ecosystem structure and functioning, and how climate controls them, at the regional scale.…”
Section: Discussionmentioning
confidence: 99%
“…; Delgado‐Baquerizo et al . ) indexes, as well as response ratios in meta‐analysis (Eldridge & Delgado‐Baquerizo ). Note that our study focuses on the simultaneous responses of multiple functions to global change rather than on the response of single functions that might not be representative of the overall functioning of a particular ecosystem.…”
Section: Methodsmentioning
confidence: 99%
“…After this, and to evaluate MRGC, we averaged the resistance of the eight functions measured to obtain a standardised index of multifunctionality resistance. Similar approaches have been used to obtain multistability (Dur an et al 2017) and multifunctionality (Maestre et al 2012;Wagg et al 2014;Delgado-Baquerizo et al 2016) indexes, as well as response ratios in meta-analysis (Eldridge & Delgado-Baquerizo 2017). Note that our study focuses on the simultaneous responses of multiple functions to global change rather than on the response of single functions that might not be representative of the overall functioning of a particular ecosystem.…”
Section: Assessing Multiple Ecosystem Functionsmentioning
confidence: 99%